The Use of Cooper's Modified Think Pair Share Technique in Improving Students' Speaking Skill - Anjaya, Annisa Defika; Bunau, Eusabinus; Wardah (IKIP Siliwangi, 2025)
This research aimed to help students at SMP Negeri 19 Pontianak improve their speaking skills by applying Cooper’s Modified Think Pair Share Technique, the latest modification of the original Think Pair Share Technique, emphasizing student-centered learning. The focus of improving speaking skills was on procedural text material related to water-saving. Students created texts on four randomly assigned topics, which included washing dishes, washing vehicles, washing clothes, and watering plants. The research employed a classroom action research method with 32 students from class 8D at SMP Negeri 19 Pontianak as the participants. The researcher collected data using observation sheets, field notes, and oral assessments. The study was conducted over two cycles. In Cycle I, students had an average score of 66.44, which increased to 71.72 in Cycle II, exceeding the Learning Objective Accomplishment Criteria (KKTP) of 71. This indicates that Cooper's Modified Think Pair Share Technique effectively enhances students’ speaking skills.